Novel Alkyl-Polyglucoside-Based Topical Creams Containing Basil Essential Oil (Ocimum basilicum L. Lamiaceae): Assessment of Physical, Mechanical, and Sensory Characteristics - Ana Barjaktarević; Georgeta Coneac; Snežana Cupara; Olivera Kostić; Marina Kostić; Ioana Olariu; Vicenţiu Vlaia; Ana-Maria Cotan; Ştefania Neamu; Lavinia Vlaia (Pharmaceutics)
Background/Objectives: Basil essential oil exhibits a wide range of biological activities, including strong antimicrobial and anti-inflammatory effects. Considering the health benefits of basil essential oil (BEO) and the favorable properties of alkyl polyglucoside emulsifiers, novel Montanov™-68-based O/W creams containing BEO were developed and characterized. Additionally, the influence of the emulsifier content on the cream’s properties was evaluated. Methods: The physicochemical properties were evaluated by organoleptic examination, physical stability test, and pH and electrical conductivity measurement. The mechanical properties were investigated by rheological, textural, and consistency analyses. In addition, a sensory evaluation protocol was applied. Results: The cream formulations containing 5% and 7% Montanov™ 68 demonstrated physical stability, with no evidence of phase separation during the observation period or following accelerated aging. The pH values remained within the acceptable range for topical use, and a gradual decrease in electrical conductivity over time was observed. The rheological analyses confirmed the non-Newtonian pseudoplastic behavior with thixotropic flow characteristics. The textural analyses demonstrated that the higher emulsifier content led to increased firmness, consistency, cohesiveness, and index of viscosity. The sensory analysis revealed differences between the alkyl polyglucoside (APG)-based cream formulations only in terms of the elasticity and stickiness. Conclusions: Although the rheological analyses suggested the better spreadability of the formulation with 5% emulsifier, this was not confirmed by the sensory analysis. However, the APG-based formulations performed significantly better than the synthetic surfactant-based formulation in terms of the absorption, stickiness, and greasiness (during and after application). These results are encouraging for the further evaluation of APG-based creams containing basil essential oil for topical application.